The Sale of Alcohol in Denmark: Recent developments and dependencies on prices/taxes - Lisbeth la Cour; Anders Milhøj (Copenhagen Business School (CBS), Department of Economics, 2005)
In the following we will analyse the sale of alcohol in Denmark. Various figures related to this question are published by Statistics Denmark at different frequencies. Our main concern will be with quarterly data for the sale of beer, wine and spirits from the period 1990 – 2004. Our two hypotheses are: First we want to convince the reader that the total sale of alcohol in Denmark since 1980 has been fairly stable. By total sale we mean the total sale of 100% alcohol so the three categories – beer, wine and spirits are measured in litres of 100% alcohol equivalents. In order to convince the reader that the total sale of alcohol has been fairly constant we will present graphs and various indicators and tests of the degree of temporal dependence in this series. The overall impression from this analysis is that our first hypothesis seems to be supported – at least not contradicted – by the data. Next, we want to model the sale of beer and wine as shares of the total sale of alcohol. Even though the total sale can be considered fairly stable there have been divergent paths of evolvement for the sub-groups: the sale of beer has decreased over the period and the sale of wine has increased. The sale of spirits has been fairly stable. Modelling the system of the beer-share and the wine-share we want to split the total development into a part that can be ascribed to changes in the relative prices and a part that can be explained by changes in taste and drinking habits specified as a trend. By specifying a system conditionally on the prices of beer, wine and spirits and a trend we manage to estimate price sensitivity and taste sensitivity. A small forecasting exercise shows that the final model is fairly good at predicting changes in the shares due to price changes. Finally, the effects on the market shares of hypothetical changes in the taxation of alcohol are discussed.
hdl:10398/7532
Keywords: H00; 330; Alcohol; Sale; drinking habits